Az e-egészségügyi megoldások fogyasztói fogadtatása Magyarországon - Lányi, Beatrix; Törőcsik, Mária (Vezetéstudomány / Budapest Management Review, 2022)
Worldwide, the use of health services via the Internet and mobile technologies is spreading rapidly. E-health technologies are accelerating health processes, improving their efficiency and increasing consumer commitment to health. eHealth technologies offer entirely new opportunities to consumers to observe and improve their health behaviours. The authors’ study is based on the results of a representative survey of 1,085 people. They explored the Hungarian population’s attitudes towards health innovations. During the examination of new health monitoring devices and applications that can be installed on smart devices, they found that their usage is not yet widespread, but consumers showed significant openness towards them. Of course, the degree of acceptance also presumes the existence of different consumer groups. The authors also examine the diffusion of applications and innovative electric devices that are used for health monitoring. Their research can serve as a starting point to track the changes caused by the pandemic.